Impact of an upper limb motion-driven virtual rehabilitation system on residual motor function in patients with complete spinal cord injury： a pilot study - Yanqing Xiao; Yang Gao; Hongming Bai; Guiyun Song; Hanming Wang; Jia-Sheng Rao; Aimin Hao; Xiaoguang Li; Jia Zheng (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Assessing residual motor function in motor complete spinal cord injury (SCI) patients using surface electromyography (sEMG) is clinically important. Due to the prolonged loss of motor control and peripheral sensory input, patients may struggle to effectively activate residual motor function during sEMG assessments. The study proposes using virtual reality (VR) technology to enhance embodiment, motor imagery (MI), and memory, aiming to improve the activation of residual motor function and increase the sensitivity of sEMG assessments. Methods By Recruiting a sample of 12 patients with AIS A/B and capturing surface electromyographic signals before, druing and after VR training, Results Most patients showed significant electromyographic improvements in activation frequency and or 5-rank frequency during or after VR training. However, one patient with severe lower limb neuropathic pain did not exhibit volitional electromyographic activation, though their pain diminished during the VR training. Conclusions VR can enhance the activation of patients’ residual motor function by improving body awareness and MI, thereby increasing the sensitivity of sEMG assessments.